OPFR removal by white rot fungi: screening of removers and approach to the removal mechanism - Losantos, Diana; Sarra, Montserrat; Caminal, Glòria (Frontiers in Fungal Biology, 2024)
The persistent presence of organophosphate flame retardants (OPFRs) in wastewater (WW) effluents raises significant environmental and health concerns, highlighting the limitations of conventional treatments for their remotion. Fungi, especially white rot fungi (WRF), offer a promising alternative for OPFR removal. This study sought to identify fungal candidates (from a selection of four WRF and two Ascomycota fungi) capable of effectively removing five frequently detected OPFRs in WW: tributyl phosphate (TnBP), tributoxy ethyl phosphate (TBEP), trichloroethyl phosphate (TCEP), trichloro propyl phosphate (TCPP) and triethyl phosphate (TEP). The objective was to develop a co-culture approach for WW treatment, while also addressing the utilization of less assimilable carbon sources present in WW. Research was conducted on carbon source uptake and OPFR removal by all fungal candidates, while the top degraders were analyzed for biomass sorption contribution. Additionally, the enzymatic systems involved in OPFR degradation were identified, along with toxicity of samples after fungal contact. Acetate (1.4 g·L-1), simulating less assimilable organic matter in the carbon source uptake study, was eliminated by all tested fungi in 4 days. However, during the initial screening where the removal of four OPFRs (excluding TCPP) was tested, WRF outperformed Ascomycota fungi. Ganoderma lucidum and Trametes versicolor removed over 90% of TnBP and TBEP within 4 days, with Pleorotus ostreatus and Pycnoporus sanguineus also displaying effective removal. TCEP removal was challenging, with only G. lucidum achieving partial removal (47%). A subsequent screening with selected WRF and the addition of TCPP revealed TCPP’s greater susceptibility to degradation compared to TCEP, with T. versicolor exhibiting the highest removal efficiency (77%). This observation, plus the poor degradation of TEP by all fungal candidates suggests that polarity of an OPFR inversely correlates with its susceptibility to fungal degradation. Sorption studies confirmed the ability of top-performing fungi of each selected OPFR to predominantly degrade them. Enzymatic system tests identified the CYP450 intracellular system responsible for OPFR degradation, so reactions of hydroxylation, dealkylation and dehalogenation are possibly involved in the degradation pathway. Finally, toxicity tests revealed transformation products obtained by fungal degradation to be more toxic than the parent compounds, emphasizing the need to identify them and their toxicity contributions. Overall, this study provides valuable insights into OPFR degradation by WRF, with implications for future WW treatment using mixed consortia, emphasizing the importance of reducing generated toxicity.